2021
DOI: 10.1186/s12940-021-00720-3
|View full text |Cite
|
Sign up to set email alerts
|

Road traffic noise, noise sensitivity, noise annoyance, psychological and physical health and mortality

Abstract: Background Both physical and psychological health outcomes have been associated with exposure to environmental noise. Noise sensitivity could have the same moderating effect on physical and psychological health outcomes related to environmental noise exposure as on annoyance but this has been little tested. Methods A cohort of 2398 men between 45 and 59 years, the longitudinal Caerphilly Collaborative Heart Disease study, was established in 1984/88… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 62 publications
0
26
0
1
Order By: Relevance
“…Previous studies had argued against this interpretation and concluded that noise sensitivity in general scarcely correlates with perception of the overall quality of the environments and would therefore only be related to the acoustic setting (see, e.g., [29]). However, Stansfeld and colleagues [30] recently showed that noise sensitivity is a specific predictor of psychological ill-health and could be part of a broader construct that they call "environmental susceptibility". The current research seems to point in this same direction.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had argued against this interpretation and concluded that noise sensitivity in general scarcely correlates with perception of the overall quality of the environments and would therefore only be related to the acoustic setting (see, e.g., [29]). However, Stansfeld and colleagues [30] recently showed that noise sensitivity is a specific predictor of psychological ill-health and could be part of a broader construct that they call "environmental susceptibility". The current research seems to point in this same direction.…”
Section: Discussionmentioning
confidence: 99%
“…Jensen, 2018 [41] Neighbour and traffic noise annoyance: a nationwide study of associated mental health and perceived stress Denmark Jensen, 2019 [47] Neighbour noise annoyance is associated with various mental and physical health symptoms: results from a nationwide study among individuals living in multi-storey housing Denmark Maschke, 2007 [46] Health effects of annoyance induced by neighbour noise France, Germany, Slovakia, Hungary, Portugal, Italy, Switzerland, Latvia Okokon, 2018 [42] Traffic noise, noise annoyance and psychotropic medication use FInland Schreckenberg, 2010 [31] Aircraft noise and quality of life around Frankfurt airport Germany Stansfeld, 2021 [39] Road traffic noise, noise sensitivity, noise annoyance, psychological and physical health, and mortality UK Table A5. Quality of evidence [22].…”
Section: Germanymentioning
confidence: 99%
“…The other items from Q9 to Q12, in fact, were related to features of reaction to noise and were not accounted for an average. In general, this approach in the data analysis is based on past studies that have highlighted the need of including the sensitivity to noise as a factor (Stansfeld et al, 2021). Furthermore, it allowed exploring the answers given to the perceived noise annoyance (Q1) considering the sample's general characteristics of gender, age range, professional sector, and city of remote working (see Tables 7, 8), and the number of people that the respondents shared the working or living environment with (see Tables 10 and 11).…”
Section: Statistical Analysesmentioning
confidence: 99%